Characteristics of Acute Myocardial Infarction Patients - Desi Natalia Trijayanti Idris; Dian Taviyanda; Srinalesti Mahanani (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Acute myocardial infarction (AMI) is a disease that has a high mortality. Usually happens to anyone and regardless of age, both male and female. The purpose of this study was to describe the characteristics of acute myocardial infarction patients hospitalized. This study uses a descriptive design. The variables used in this study were the characteristics of acute myocardial infarction patients consisting of gender, age, education, history of hypertension, history of diabetes mellitus, family history of acute myocardial infarction, blood pressure and pulse frequency. The number of samples used was 35 respondents who analyzed the data using a frequency distribution. The results showed that the characteristics of 35 respondents showed that the majority of AMI patients occurred in men, namely 60%, the majority were aged 56-60, namely 34.3%, the majority had a history of hypertension, diabetes mellitus and also a family history of having AMI.